Stretch Bend Testing of High Strength Low Alloy Sheet Steels - Bansal, Anil K. (My University, 1977)
The stretch bend test has been used to investigate the formability of a series of high strength, low-alloy sheet steels with yield strengths in the range 35 to 90 ksi, varying compositions and inclusion shapes.
The results of the stretch bend tests have been compared with those of tensile, hole expansion and punch stretching tests on the same steels to obtain an indication of the sensitivity of the test to steel quality. In addition sone stretch bend tests have been carried out to investigate the influence of varying the lubrication, specimen width and specimen span in the test.
The results show that the stretch bend is somewhat insensitive to the presence of elongated inclusions at the lower strength levels and inclusion contents but this sensitivity does increase with increasing test span and should be adequate at the larger spans. Local strains at fracture in both tensile and stretch bend tests give a more reliable indication of the presence elongated inclusions. Of the bulk formability measurements the hole expansion limit exhibits the greatest sensitivity to steel quality.
Keywords: Engineering; Engineering